Klasyfikacja otwartych funduszy emerytalnych ze względu na strategię zarządzania na podstawie analizy stylu Sharpe'a - Orwat, Agnieszka (The classification of the Open Pension Funds (OPF) in terms of a management strategy based on sharpe's style analysis, 2006)
The article discusses the attempt to implement the style analysis to define the exposition to varied returns on asset classes within portfolios of the Open Pension Funds which operate on the Polish financial market, followed by the attempt to classify the OPFs in terms of management strategies based on the results of Sharpe’s style analysis. Classification methods applied: the K-mean method and selected hierarchical methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 553-561